The Role of Speckle-Tracking Strain Echocardiography in the Clinical Evaluation and Follow-up of Myocarditis with Preserved Ejection Fraction: A Case Report - Ardhestiro Hanindyo Putro (Perkumpulan Kedokteran Militer, 2024)
Introduction: Myocarditis has heterogeneous clinical manifestations and may be difficult to recognize when left ventricular ejection fraction is preserved. Speckle-tracking echocardiography may detect subtle myocardial dysfunction through global longitudinal strain (GLS) assessment. Case Illustration: A 30-year-old woman presented with exertional dyspnea and preceding sore throat, followed by chest pain radiating to the left shoulder. Electrocardiography showed sinus rhythm without acute ST-segment elevation, and conventional transthoracic echocardiography showed preserved LVEF (61%). Inflammatory markers and NT-proBNP were elevated. STE demonstrated markedly reduced GLS (-4.7%), especially in lateral, posterior, and anterior segments. Cardiac magnetic resonance imaging performed 10 days after symptom onset showed subepicardial late gadolinium enhancement in the basal lateral and inferolateral left ventricular walls, supporting myocarditis. Discussion: The regional distribution of impaired strain corresponded with cardiac magnetic resonance abnormalities, suggesting that STE may identify clinically relevant myocardial involvement despite normal LVEF. Serial STE showed improvement during follow-up after guideline-directed therapy and clinical stabilization. Conclusion: GLS assessment by STE is a useful non-invasive adjunct for diagnosis, risk evaluation, and follow-up of suspected myocarditis, particularly when conventional echocardiography appears normal.